High energy synchrotron X-ray measurements of 2D residual stress states in metal matrix composites - Korsunsky, A; Wells, K (Trans Tech Publications, 2000)
The advent of the high intensity, high energy sychrotron X-ray beamlines at the European Sychrotron Radiation Facility at Grenoble has presented the residual stress measurement community with some unprecedented opportunities, as well as challenges. In order to explore the capabilities and limitations of the new instruments, we have studied residual and in situ loading strain distributions in a number of metal matrix composite systems, using BM16 the Powder Diffraction beamline, and ID11, the Materials Science beamline, at ESRF. In this paper, we discuss the methods of data analysis, error estimation, and measurement interpretation, and present some results for both particulate and fibre-reinforced materials.